2014
DOI: 10.1080/00397911.2013.854916
|View full text |Cite
|
Sign up to set email alerts
|

o-Iodoxy Benzoic Acid–Mediated Synthesis of 3,5-Diarylisoxazoles and Isoxazole-3-carboxylic Acids

Abstract: IR spectra were recorded on IRPrestige-21, Shimadzu FTIR spectrophotometer. 1 HNMR spectra were obtained on a Avance Bruker-400MHz spectrometer and 13 C NMR were obtained on a Avance Bruker-75MHz spectrometer., Samples were analysed in CDCl 3 and the chemical shift

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The most important methods described so far for the synthesis of 3,5‐isoxazoles are the condensation of 1,3‐diketones with hydroxylamine and the [3+2] dipolar cycloaddition between alkynes and nitrile oxides . In this context, oxidation of oxime was promoted by Magtrieve TM (Sigma‐Aldrich, France) (CrO 2 ), alkyl nitrites, IBX, or more often by N ‐chlorosuccinimide . This latter procedure was privileged for our synthetic strategy to obtain target isoxazolyl‐dimethoxytriazines 3 starting from oximes 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The most important methods described so far for the synthesis of 3,5‐isoxazoles are the condensation of 1,3‐diketones with hydroxylamine and the [3+2] dipolar cycloaddition between alkynes and nitrile oxides . In this context, oxidation of oxime was promoted by Magtrieve TM (Sigma‐Aldrich, France) (CrO 2 ), alkyl nitrites, IBX, or more often by N ‐chlorosuccinimide . This latter procedure was privileged for our synthetic strategy to obtain target isoxazolyl‐dimethoxytriazines 3 starting from oximes 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Dose-dependent inhibitory effect of compounds 2a and 2b is shown in figure 4. In the literature various substituted chalcone compounds such as; sulfonamide chalcone, 42-43 3',5'-digeranylated chalcone, 44 aminochalcones, 42 and the other substituted chalcone compounds 42,45 were mentioned to be potent inhibitor against α-glucosidase. In our case, screening of the hydroxyl and methoxy substituted chalcone oximes compounds (2a-2k) against α-glucosidase revealed that hydroxyl substituted chalcone oximes 2a and 2b were found to be the best inhibitor against αglucosidase activity.…”
Section: α-Glucosidase Inhibitory Activity Of Compounds 2a-2kmentioning
confidence: 99%
“…Nonetheless, the latter methods commonly require the use of stoichiometric amounts of oxidants, such as TEMPO, hypervalent iodine, DDQ, metal salt and so on, which caused heavy burden to the environment. [41][42][43][44][45][46] It is no doubt that the catalyzed oxidation with pure oxygen or air as the oxidant is a green solution. Herein, we disclose a new copper(II)-catalyzed synthesis of 3,5-disubstituted isoxazoles from enone oximes through a C-H functionalization/C-O bond-forming process that uses oxygen as the terminal oxidant and water as the only direct waste product.…”
mentioning
confidence: 99%